Walking to Listen :4000 Miles Across America, One Story at a Time - Andrew Forshoefel (Bloomsbury, 2017)
Life is fast, and I’ve found it’s easy to confuse the miraculous for the mundane, so I’m slowing down, way down, in order to give my full presence to the extraordinary that infuses each moment and resides in every one of us.